APPLICATION OF THE CHARTER TO UNIVERSITIES’ LIMITATION OF EXPRESSION - Newman, Dwight (Revue de droit de l'Université de Sherbrooke)

(untitled) (Revue de Droit de l’Université de Sherbrooke, 2015)
The Canadian Charter of Rights and Freedoms applies only to governmental action. As a result of this limited scope of application, there have been significant questions concerning its application to post-secondary education contexts. Although early case law appeared to establish universities as a Charter-free zone, later cases have made clear that this is not the case. This paper uses Justice Deschamps’s rearticulated rule on Charter application to make this point clear, shows that this revised approach is showing itself in case law, and challenges claims that academic freedom gives reasons not to see Charter application in a university context. Indeed, the paper argues that in the present context, Charter application actually seems likely to further the values of academic freedom.